Eosinophilic granulomatous polyangiitis with central nervous system involvement in children: a case report and literature review - Nie, Nana; Liu, Lin; Bai, Cui; Wang, Dahai; Gao, Shan; Liu, Jia; Zhang, Ranran; Lin, Yi; Zhang, Qiuye; Chang, Hong (Frontiers in Immunology, 2024)
Objective To explore the clinical characteristics and treatment outcomes of children with central nervous system (CNS) involvement in eosinophilic granulomatosis with polyangiitis (EGPA). Methods A child who presented with EGPA complicated by CNS involvement was admitted to our hospital in June 2023. The clinical features were analyzed retrospectively, and relevant literatures were reviewed to provide a comprehensive overview of this condition. Results A ten-year-old girl, who had a history of recurrent cough and asthma accompanied by peripheral blood eosinophilia for eight months, was admitted to our hospital. On admission, spotted papules were visible on her hands and feet, bilateral pulmonary rales were audible. The laboratory examination revealed that the proportion of eosinophils (EOS) exceeded 10% of white blood cells, the anti-neutrophil cytoplasmic antibody (MPO-ANCA) was positive, the immunoglobulin G level was 15.80g/L, and the immunoglobulin E level was greater than 2500.00IU/mL. The imaging examination showed multiple patchy and nodular high-density shadows in both lungs as well as sinusitis. Pulmonary function tests indicated moderate ventilation and diffusion dysfunction. Bone marrow cytology demonstrated a significant increase in the proportion of eosinophils. Skin pathology confirmed leukocytoclastic vasculitis. During the hospitalization, the child had a convulsion. The magnetic resonance imaging (MRI) scan of the brain showed multiple abnormal signal shadows in the bilateral cerebral cortex and the electroencephalogram (EEG) showed epileptic waves. Following the administration of methylprednisolone pulse therapy in combination with cyclophosphamide treatment, her cough and asthma resolved, the skin rash disappeared without any further convulsions. We found that only a young EGPA patient with CNS involvement had been previously reported. The previously reported case began with long-term fever, weight loss, and purpuric rash. Both patients responded well to treatment with glucocorticoids and cyclophosphamide, experiencing significant improvement in their clinical symptoms and normalization of their peripheral blood eosinophils. Conclusion The diagnosis of EGPA in children can be challenging. When a child is affected by EGPA, it is essential to remain vigilant for signs of CNS involvement. The treatment with glucocorticoids and cyclophosphamide is effective in managing EGPA in children.